Effectiveness of thymol in extending keeping quality of cottage cheese - Makhal, Subarna (Springer India, 2012)
Direct acidified cottage cheese has a limited shelf life of 10–12 days under refrigeration due to high moisture content (~75 %) and a relatively high pH (~5.0). This affects its widespread marketing and distribution. Hence, a study was undertaken to improve the shelf life of direct acidified cottage cheese using thymol, a phytophenolic natural antimicrobial agent. The effect of three different levels, i.e. 30, 40 and 50 ppm of 30 % thymol solution in butteroil on the physico-chemical, microbiological and organoleptic properties was studied at four-day interval during storage under refrigeration (4–5 °C). Promising results were obtained using 40 ppm thymol for inhibiting psychrotrophs, yeasts and molds as well as retarded the proteolysis in cottage cheese. Based on the effect on flavour of the fresh samples as well as the extent of changes in quality during storage, it was observed that addition of 40 ppm thymol enhanced the keeping quality of cottage cheese by 8 days compared to the control sample.